Foreword - Vol 5 - Editorial Board, (Irish Journal of Arts Management and Cultural Policy, 2019)
The board has recently reviewed the editorial policy of the Irish Journal of Arts Management and Cultural Policy. The exercise was prompted by our desire to provide a more diverse, representative and inclusive platform for academics and emerging researchers, those involved in both creative and management practice in the cultural sector, and policymakers, to engage with questions of policy and management on cultural issues across the island of Ireland. While maintaining our existing commitment to publishing original academic research papers, the new policy seeks to highlight emerging research from the wealth of student work at MA level on the island, and provide an opportunity for cultural managers, practitioners and policymakers to reflect on policies and practices shaping the cultural sector here.